The Impact of Target Frequency on Intra-Individual Variability in Euthymic Bipolar Disorder: A Comparison of Two Sustained Attention Tasks - Moss, Rachel Ann; Finkelmeyer, Andreas; Robinson, Lucy J.; Thompson, Jill M.; Watson, Stuart; Ferrier, I. Nicol; Gallagher, Peter (Frontiers in Psychiatry, 2016)
Greater intra-individual variability (IIV) in reaction time (RT) on a sustained attention task has been reported in patients with bipolar disorder (BD) compared with healthy controls. However, it is unclear whether IIV is task-specific, or whether it represents general cross-task impairment in BD. The present study aimed to investigate whether IIV occurs in sustained attention tasks with different parameters. Twenty-two patients with BD (currently euthymic) and 17 controls completed two sustained attention tasks on separate occasions: a low target frequency ( 20%) Vigil Continuous Performance Test (CPT), and a high target frequency ( 70%) CPT version A-X (CPT-AX). Variability measures (individual standard deviation and coefficient of variation) were calculated per participant, and ex-Gaussian modeling was also applied. This was supplemented by Vincentile analysis to characterize RT distributions. Results indicated that participants (patients and controls) were generally slower and more variable when completing the Vigil CPT, compared to CPT-AX. Significant group differences were also observed in the Vigil CPT, with euthymic BD patients being more variable than controls. This result suggests that IIV in BD demonstrates some degree of task-specificity. Further research should incorporate analysis of additional RT distributional models (Drift Diffusion and Fast Fourier Transform), to fully characterize the pattern of IIV in BD, as well as its relationship to cognitive processes.